Konsep Pendidikan Akhlak: Perspektif Al-Qur’an - Putri Halimaini K; Asnil Aidah Ritonga; Mohammad Al Farabi (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The Qur’an, as the holy book of Muslims, has provided complete guidance on moral education. However, many people feel the need to question and understand more deeply how moral education is taught in the Koran and how it is relevant to the current context of life. Moral education is to form people who are faithful, devout, have noble character, are advanced and independent so that they have high spiritual resilience and are able to adapt to the dynamics of societal development. In the article, the focus is on the verses about moral education in QS Luqman verses 12-19; QS Al Hujurat verses 11-13; An Nur verse 31; QS Al Ahzab verse 59